Application of Microbial Biopolymers as an Alternative Construction Binder for Earth Buildings in Underdeveloped Countries - Ilhan Chang; Minkyung Jeon; Gye-Chun Cho (International Journal of Polymer Science)
Earth buildings are still a common type of residence for one-third of the world’s population. However, these buildings are not durable or resistant against earthquakes and floods, and this amplifies their potential harm to humans. Earthen construction without soil binders (e.g., cement) is known to result in poor strength and durability performance of earth buildings. Failure to use construction binders is related to the imbalance in binder prices in different countries. In particular, the price of cement in Africa, Middle East, and Southwest Asia countries is extremely high relative to the global trend of consumer goods and accounts for the limited usage of cement in those regions. Moreover, environmental concerns regarding cement usage have recently risen due to high CO2 emissions. Meanwhile, biopolymers have been introduced as an alternative binder for soil strengthening. Previous studies and feasibility attempts in this area show that the mechanical properties (i.e., compressive strength) of biopolymer mixed soil blocks (i.e, both 1% xanthan gum and 1% gellan gum) satisfied the international criteria for binders used in earthen structures. Economic and market analyses have demonstrated that the biopolymer binder has high potential as a self-sufficient local construction binder for earth buildings where the usage of ordinary cement is restricted.